2004
DOI: 10.1017/s0714980800016834
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Life Patterns and the Residential Mobility of Older Men

Abstract: There are numerous ways to better integrate the elderly into communities, many of which are contingent upon whether they will remain in their pre-retirement homes or make a move. Using a life course perspective, this paper establishes that residential history, social and family relations, socio-economic status, and health trajectories measured at mid-life can be associated with moves in later life, either directly, or indirectly through their effect on the mid-life residential trajectory. These relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Although Sauer et al (2011) found that gender had no influence on response consistency, we decided to include it in our analysis because previous research has shown gender-specific differences in attitudes to the topic of residential mobility (Hayward, 2004;Teti, Kuhlmey, Dräger, & Blüher, 2012). Because gender-specific differences in response consistency in this age cohort can be expected to be conditional on differences in educational and occupational trajectories (for which we controlled), we did not expect to find an independent effect of gender on response consistency.…”
Section: Housing Opportunities and Mobility In The Elderly (Home) Feasimentioning
confidence: 99%
“…Although Sauer et al (2011) found that gender had no influence on response consistency, we decided to include it in our analysis because previous research has shown gender-specific differences in attitudes to the topic of residential mobility (Hayward, 2004;Teti, Kuhlmey, Dräger, & Blüher, 2012). Because gender-specific differences in response consistency in this age cohort can be expected to be conditional on differences in educational and occupational trajectories (for which we controlled), we did not expect to find an independent effect of gender on response consistency.…”
Section: Housing Opportunities and Mobility In The Elderly (Home) Feasimentioning
confidence: 99%
“…The life course model suggests that patterns of geographic mobility vary across the life course, and that geographic mobility in later life is influenced by age-related life course events such as children leaving home, retirement, death of a spouse, declines in health, and reductions in income. Furthermore, life course trajectories at mid-life can influence moves in later life (Hayward, 2004).…”
Section: Progress In Research On the Geographic Mobility Of Seniorsmentioning
confidence: 99%
“…Since the mid-1980s, population surveys have matured and some of these surveys contain data on the geographic mobility of older Canadians. For example, studies of elderly mobility have been conducted by Sarma, Hawley, and Basu (2009) using the first six cycles (1994–1995 to 2004–2005) of the ongoing Canadian longitudinal National Population Health Survey; Sarma and Simpson (2007) drew on the longitudinal Aging in Manitoba study (with data from 1971 to 2001); Ostrovsky (2004) used the longitudinal Canadian Survey of Labour and Income Dynamics from 1996–2000; Hayward (2004) made use of the Ontario Longitudinal Study on Aging 1959–1978; Gee, Kobayashi, and Prus (2004) drew on the Canadian Community Health Survey of 2000–2001; Moore and Rosenberg (1994, 1997) used both the 1991 Survey on Aging and Independence and the 1986 and 1991 Health and Activity Limitation Survey; and Bergob (1995) employed the 1990 General Social Survey. The Canadian Longitudinal Study on Aging (CLSA) which, at the time of this writing, had begun the first wave of data collection, promises to produce a rich data set for future research (Martin-Matthews & Mealing, 2009; Raina et al, 2009).…”
Section: Progress In Research On the Geographic Mobility Of Seniorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of related themes have been identified in the literature as influencing the decision to move. Chief among these is the life-cycle, essentially the decisions that are made by a household based on factors such as age, family, education and work career (Hayward 2004). Another theme is the affect of socio-economic status (SES), particularly as related to ethnicity in the United States (Frey 1979;St.…”
Section: Introductionmentioning
confidence: 99%